Correction: In Porphyromonas gingivalis VimF Is Involved in Gingipain Maturation through the Transfer of Galactose. - Arun S Muthiah; Wilson Aruni; Antonette G Robles; Yuetan Dou; Francis Roy; Hansel M Fletcher (PLoS ONE, 2019)
[This corrects the article DOI: 10.1371/journal.pone.0063367.].